The Problem of Quality and Efficiency of Educational Institution Management - Svitlana Polishchuk; Oksana Horbatiuk (Vasyl Stefanyk Precarpathian National University, 2023)
The article researches and substantiates the problem of quality and efficiency of educational institution management, describes the transformation processes that take place in Ukraine at this stage, and reveals the existing problems. The article reveals the strategic tasks of reforming the management process of educational institutions. The authors justified ways to implement these tasks. At the same time, the authors of the article pay attention to the lack of readiness of heads of educational institutions for professional management activities and the lack of the necessary managerial competence in many of them, emphasizing the need to form a new generation of leaders. The authors emphasize the importance of the role of the head of an educational institution in introducing the latest educational technologies into the educational process, forms and methods of teaching, upbringing, and development of the individual, and so on. At the same time, special attention is paid to the need to improve the management system, and attention is focused on the importance of making managerial decisions. Considerable attention is paid to the importance of the management decision made by the manager of an educational institution in ensuring the goal. Among other things, the authors draw attention to the importance of directing the entire scientific and educational potential to ensure the high efficiency of the educational institution's activities. The article specifies the criteria used to evaluate the activities of an educational institution. The authors emphasize the spheres of influence of the quality of management on the activities of an educational institution, name the factors that directly affect the management process, and draw our attention to the importance of the level of professionalism of the head (manager) of an institution of general secondary education. The authors also pay attention to properties that contribute to improving the quality and efficiency of the management process. At the same time, the authors focus our attention on the effectiveness of management systems. In this context, special attention is paid to the choice of approaches that contribute to successful quality assurance of educational institution management, while emphasizing their advantages and highlighting their disadvantages. The article emphasizes the involvement of the teaching staff of an educational institution in management activities. At a high professional level, the topic of the article is revealed, the tasks of writing it are defined, and the level of potential for implementing the management process of educational institution managers is studied and justified. The Conclusions Drawn by the authors of the article are specific and fully correspond to the content of the work.